A Conceptual Model for Mind Management to Cultivate Mental Immunity for Life Based on the Abhidhamma Buddhist Psychology - Phyo Pyae Sone Kyaw; Phramaha Nanthakorn Piyabhani; Sanu Mahatthanadull (The Journal of International Buddhist Studies College, 2025)
This qualitive research has three main objectives, namely: 1) To examine the concept of mental immunity and its management according to psychology; 2) To study the concept of mind and its process in Abhidhamma; and 3) To develop a conceptual model for mind management to cultivate mental immunity for life based on the Abhidhamma Buddhist psychological perspective. This dissertation employs a qualitative research method, drawing on both primary and secondary sources. The field study involved in-depth interviews with subject-matter experts in both Abhidhamma and modern psychology. The research findings reveal that the mind plays a central role in emotional experiences and can be managed to cultivate mental immunity, based on the Abhidhamma Buddhist psychological perspective. A Conceptual Model for Mind Management to Cultivate Mental Immunity for Life, Based on the Abhidhamma Buddhist Psychology, would address three main purposes. First, the findings highlight how modern psychology views mind management, indicating that poor communication, negative thinking, and environmental stress contribute to emotional disturbances. Psychological methods, such as behavioral change and cognitive restructuring, have been shown to be effective in managing anger and promoting mental well-being. Second, it studies the concept of the mind and its processes from the Abhidhamma viewpoint, where the mind is regarded as the source of emotions, thoughts, and actions. From this perspective, negative emotions such as anger, sadness, and depression stem from unwholesome mental states, potentially leading to social conflict, violence, and even war. Third, the study develops a conceptual model for mind management to cultivate mental immunity for life utilizing Abhidhamma-based Buddhist psychological approaches. These include behavioral change through purity in actions and speech, cognitive restructuring by identifying and replacing negative thoughts, and wisdom-based practices such as mindfulness and wise attention to transform anger at its root. Through the integration of these approaches, individuals can develop emotional resilience, reduce anger, and cultivate a peaceful state of mind, offering a practical model for managing the mind in today’s world.